Autism spectrum disorder: reconceptualising support for neurodiverse students in higher education. Issue 2 (4th March 2023) - Evans, Dena; Granson, Matthew; Langford, David; Hirsch, Sophie
ABSTRACT: The number of students with ASD entering higher education is increasing. Ensuring that appropriate support structures are in place is imperative for their academic, social, and personal success. However, research on students with ASD often does not include student perspectives. Mismanagement of students' transition into higher education institutions, coupled with a general lack of knowledge regarding their unique needs, can lead to anxiety, stigmatisation, bullying, and poor performance. The objective of this cross-sectional mixed-methods study was to explore the academic, social, institutional, and environmental challenges of students with ASD. Convenience sampling resulted in a sample of 74 students enrolled at a large, urban research university in the southeastern United States. Findings revealed significant differences between gender and use of support services, diagnosis disclosure, social engagement, and difficulties interacting with neurotypical people in an environment often perceived as ill-equipped to provide support. Consequently, potential institutional, programmatic, and policy implications emerged.